A Study on The Technical Innovation And Purchase Intention In Online Shopping Industry In China - Chen, Guan Yu (International Journal of Psychosocial Rehabilitation, 2020)
Technology is innovated in a high speed, like the 5G taking place of 4G currently, and online shopping development has contribution to the national economy improvement in the recent years. Hence, this research is to study the relationship between the technical innovation and purchase intention in the online shopping in Chinese market, with the mediator variables perceived ease of use, convenience, technological competence, media richness, and the accessibility. In this research, the correlation questionnaires are distributed to the target respondents who are the customers in online shopping industry with the online shopping experiences in the cities, which are innovated with the 5G technology in 2019 in China. With 298 respondents’ feedback, the relationship between technical innovation and the purchase intention will be analysed with the multiple regression analysis. There is significant relationship between technical innovation and purchase intention and technical innovation can improve the convenience, technological competence, media richness, the accessibility and the purchase intention in online shopping industry. The technical innovation influences the accessibility and media richness most, and accessibility has the highest influence on the purchase intention. But technical innovation cannot positively influence the perceived ease of use, and with the technical innovation, the perceived ease of use cannot positively influence the purchase intention in the online shopping in Chinese market. Based on the relationship between technical innovation and purchase intention in the online shopping industry in China, this study gives some practical implications to the online shopping development with the technical innovation. With the study on the technical innovation in China, the “Chinese model” online shopping industry may be applied and developed in other nations and markets.